Modeling and characterizing errors in satellite and reanalysis precipitation estimates using a two-step decomposition procedure - Zhehui Shen; Mingze Ding; Ruochen Huang; Hao Wu; Bin Yong (Journal of Hydrology, 2026)

Overcoming acidic constraints: A bio-inspired cu-bilirubin nanozyme with superior neutral-pH peroxidase and laccase-like activities for selective sensing and removal of formaldehyde and pyrogallic acid - Ruochen Duan; Xiaohui Hao; Ao Shen; Panqing Zhang; Zeyu Zhang; Xuebing Wang; Long Chen; Qingyang Fan; Jiahao Wang; Yunxu Yang (Chemical Engineering Journal, 2026)

Urinary total arsenic, arsenic species, and arsenic methylation capacity: an integrative profiling analysis of microRNAs in plasma and leukocytes - Yaxin Wang; Wending Li; Weiya Li; Yufei Wang; Xuedan Xu; Ruochen Yuan; Xiao Zhang; Jingli Qu; Pinpin Long; Hao Wang; Meian He; Xiaomin Zhang; et al. (Environmental Pollution, 2026)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Dairy farm waste: A potential reservoir of diverse antibiotic resistance and virulence genes in aminoglycoside- and beta-lactam-resistant Escherichia coli in Gansu Province, China - Muhammad Shoaib; Minjia Tang; Amjad Islam Aqib; Xuejing Zhang; Zhongyong Wu; Yang Wen; Xiao Hou; Jinpeng Xu; Ruochen Hao; Shengyi Wang; Wanxia Pu (Environmental Research, 2024)

A comprehensive investigation of three long‐term precipitation datasets: Which performs better in the Yellow River basin? - Ruochen Huang; Bin Yong; Fan Huang; Hao Wu; Zhehui Shen; Da Qian (International Journal of Climatology, 2024)
The fifth generation European Centre for Medium‐Range Weather Forecasts Reanalysis on global land surface (ERA5‐Land), the Multi‐Source Weighted‐Ensemble Precipitation (MSWEP), and the Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) are three representative precipitation estimates with quasi‐global coverage, high‐resolution and long‐term record. This study concentrates on investigating, for the first time, the long‐term spatiotemporal accuracy and regional applicability of these precipitation estimates at a daily scale in the Yellow River basin (YRB) using 39 complete years of data record (1981–2019), with a special focus on their capability on monitoring the extreme precipitation events with short duration and the continuous heavy precipitation events. Results indicate that MSWEP generally performs better than ERA5‐Land and CHIRPS in almost all seasons and subregions, with the highest Pearson correlation coefficient and critical success index, lowest root mean square error and false alarm ratio. ERA5‐Land presents a severe overestimation of precipitation amount, particularly in the plateau climate region (BIAS = 52.27%), but well reflects its spatial–temporal patterns in the YRB. As for the detecting capability, MSWEP shows the best accuracy in detecting extreme precipitation, particularly in maximum consecutive 5‐day precipitation (RX5day). The MSWEP better represents the spatial distribution of maximum 1‐day precipitation and maximum consecutive 5‐day precipitation in the YRB, but it shows a significant overestimation in zone Southern Qinghai. MSWEP and CHIRPS have better performance of temporal variation consistency in annual precipitation with ground reference than ERA5‐Land, while ERA5‐Land performs well in capturing extreme precipitation temporal variation, especially for continuous heavy precipitation events. This study can provide useful guidance when choosing long‐term precipitation products for hydrometeorological applications and climate‐related studies in the YRB.

Fabrication of a porous Urea@MIL-100(Fe)/CI-MCC/SA hydrogel for All-In-One adsorption, removal and fluorescence monitoring of nitrite - Xiaohui Hao; Ao Shen; Ruochen Duan; Panqing Zhang; Lingwei Xue; Xiuqing Zhao; Xuebing Wang; Xue Li; Yunxu Yang (Journal of Hazardous Materials, 2024)

Suppression of phosphorus release and acceleration of sediment consolidation via exposure to sunlight and air (sunbathing) - Hao Hou; Wei Zhu; Jiming Liu; Xiaowei Lin; Ruochen Wang; Santao Xie; Hongyong Wu (Journal of Soils and Sediments, 2024)

Simple method for visual detection of nitrite using fluorescence and colorimetry by poly (tannic acid) nanoparticles - Xiaohui Hao; Ao Shen; Mengwen Li; Ruochen Duan; Lala Hou; Xiuqing Zhao; Ziqi Li; Yongwei Zhao; Panqing Zhang; Xuebing Wang; Xue Li; Yunxu Yang (Analytica Chimica Acta, 2023)

Mechanism of Water Inrush Through Fault Zones Using a Coupled Fluid–solid Numerical Model: A Case Study in the Beiyangzhuang Coal Mine, Northern China - Wenping Mu; Xiong Wu; Ruochen Deng; Qian Hao; Cheng Qian (Mine Water and the Environment, 2020)